Effects of feeder design and pellet quality on finishing pigs - N Amornthewaphat; Joe D Hancock; Keith C Behnke; Leland J McKinney; C W Starkey; D J Lee; C L Jones; J S Park; D W Dean (Kansas Agricultural Experiment Station Research Reports, 2000)
Pigs fed from wet/dry feeders had 2.5% greater ADG and used 26% less water compared to pigs fed from conventional dry feeders. Also, as percentage fines was increased from none to 50%, ADG and digestibilities of DM and N decreased. However, the decreased ADG with increased pellet fines occurred only with the conventional dry feeder.; Swine Day, Manhattan, KS, November 16, 2000
Keywords: Swine day; 2000; Kansas Agricultural Experiment Station contribution; no. 01-138-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 858; Swine; Pellet quality; Wet/dry feeders; Finishing pigs